2005
DOI: 10.1002/bit.20673
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of oxygen carrier mediated oxygen transport to C3A hepatoma cells housed within a hollow fiber bioreactor

Abstract: A priori knowledge of the dissolved oxygen (O2) concentration profile within a hepatic hollow fiber (HF) bioreactor is important in developing an effective bioartificial liver assist device (BLAD). O2 provision is limiting within HF bioreactors and we hypothesize that supplementing a hepatic HF bioreactor's circulating media with bovine red blood cells (bRBCs), which function as an O2 carrier, will improve oxygenation. The dissolved O2 concentration profile within a single HF (lumen, membrane, and representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 65 publications
3
34
0
Order By: Relevance
“…Also, mPEG-bRBCs could be cross-linked with gluteraldehyde to further alter the P 50 for oxygenation in bio-artificial devices (Gordon et al, 2005;Sullivan et al, 2006). Before application of this novel blood substitute, the most important concern will be the safety of the bovine blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…Also, mPEG-bRBCs could be cross-linked with gluteraldehyde to further alter the P 50 for oxygenation in bio-artificial devices (Gordon et al, 2005;Sullivan et al, 2006). Before application of this novel blood substitute, the most important concern will be the safety of the bovine blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated by extensive simulation work conducted in our lab. [19][20][21][22] Recent experimental studies also showed that supplementation of bovine red blood cells (bRBCs) into the circulating cell culture medium improved O 2 transport to cultured C3A cells in a HF bioreactor. 23,24 In the presence of bRBCs, the molar ratio of lactate production to glucose consumption of hepatoma cells was remarkably reduced, while albumin synthesis increased substantially, which indicates highly efficient cellular metabolism and synthetic function.…”
mentioning
confidence: 99%
“…108 Besides implementing MM oxygen consumption of hepatocytes, hemoglobin model as an oxygen carrier is also included.…”
Section: Computer Fluid Dynamic "Cfd… Modeling Of Ebalmentioning
confidence: 99%